2018
DOI: 10.3390/su10082666
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Spontaneous Spreading of Stone Bunds in Ethiopia: Implications for Sustainable Land Management

Abstract: This study deals with the spontaneous spreading of stone bunds in the central Ethiopian highlands, i.e., the adoption and implementation of stone bunds by farmers on their own initiative. The study tests the hypothesis that spontaneously implemented stone bunds, as compared to stone bunds implemented by mass mobilization campaigns, are more integrated with other land management practices and lead to higher yields. Data are collected in the Girar Jarso woreda through field observations and household surveys. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 45 publications
2
18
0
12
Order By: Relevance
“…Moreover, compared with the NSF, SF are farmers with better knowledge as well as experience in IFM. This was also observed in a previous study that showed that spontaneously implemented stone bunds were more integrated with compost and manure use to produce high yields and sufficient crop residues for livestock feeds (Abi et al 2018). Results also indicate that SF have a better farm planning and more positive future prospects to change and to make improvements in their household food security and living condition and therefore have a longer planning horizon than the NSF.…”
Section: Farmer Socio-cultural Characteristicssupporting
confidence: 68%
See 4 more Smart Citations
“…Moreover, compared with the NSF, SF are farmers with better knowledge as well as experience in IFM. This was also observed in a previous study that showed that spontaneously implemented stone bunds were more integrated with compost and manure use to produce high yields and sufficient crop residues for livestock feeds (Abi et al 2018). Results also indicate that SF have a better farm planning and more positive future prospects to change and to make improvements in their household food security and living condition and therefore have a longer planning horizon than the NSF.…”
Section: Farmer Socio-cultural Characteristicssupporting
confidence: 68%
“…Work motivation is directly related to the perception that farmers have on implemented stone bunds. Results also show that SF have a more positive perception of stone bunds than the NSF, which is of course due to the experienced positive effects of stone bunds on soil erosion, soil productivity and crop yields (Abi et al 2018). Not surprisingly, results also show that SF have a better sense of ownership and responsibility to protect and maintain implemented stone bunds than NSF.…”
Section: Farmer Socio-cultural Characteristicssupporting
confidence: 54%
See 3 more Smart Citations